2021
DOI: 10.5114/pedm.2021.105634
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of osteoporosis preventive behaviors among adolescent: a cross-sectional study

Abstract: Background: Osteoporosis is a preventable progressive metabolic disease. Girls have an increased risk of occurrence of osteoporosis in their old age. The BASNEF model can be employed to change behaviors related to health. Aim of the study: The BASNEF model was employed to determine the predictors of osteoporosis preventive behaviors among adolescent girls. Material and methods: This cross-sectional study was carried out on 209 adolescent girls selected from high schools in the Quchan County in 2016 using path … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In the same line as the present study, Kang and Kim tried to explore the predictors of OPB among women in their 20 s and 30 s. They elaborated that women with higher osteoporosis-related knowledge had significantly higher healthy behaviors and had at least one weight control experience [36]. Moreover, Rastgoo et al conducted a study to investigate the predictors of OPB among adolescents and found an indirect effect of knowledge on OPB via the intermediary roles of attitudes and behavioral intention [37].…”
Section: Discussionmentioning
confidence: 76%
“…In the same line as the present study, Kang and Kim tried to explore the predictors of OPB among women in their 20 s and 30 s. They elaborated that women with higher osteoporosis-related knowledge had significantly higher healthy behaviors and had at least one weight control experience [36]. Moreover, Rastgoo et al conducted a study to investigate the predictors of OPB among adolescents and found an indirect effect of knowledge on OPB via the intermediary roles of attitudes and behavioral intention [37].…”
Section: Discussionmentioning
confidence: 76%
“…The current study shows that gender, osteoporosis knowledge, perceived susceptibility, exercises’ perceived benefits, perceived barriers to exercises, and calcium and health motivations were associated with high OPB. In the same line, Rastgoo et al examined the predictors of OPB using the BASNEF model and reported that it was significantly associated with osteoporosis related knowledge [ 55 ]. Furthermore, Elgzar et al found that knowledge and health beliefs related to osteoporosis were significantly associated with OPB among premenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…The low rate seems to be attributable to the fact that we used a self-report questionnaire to determine whether the respondent had been diagnosed with osteoporosis or osteopenia. Because osteoporosis is a preventable progressive metabolic disease, [ 23 ] reducing the future prevalence of osteoporosis requires reducing reduction in the risk of future osteoporosis in young adults. [ 24 ] Therefore, management and early screening of osteoporosis or osteopenia in women in their 20s and 30s are important, as this is the golden period for osteoporosis prevention.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] There was a positive and direct relationship between knowledge and attitudes on osteoporosis prevention, the intention and osteoporosis prevention behavior, and subjective norms and osteoporosis prevention behavior. [23] Further, the rate of regular exercise was 1.28 times higher among single-person households than multiperson households, [25] calling for further research on the health behaviors of single-person households of women in their 20s and 30s.…”
Section: Discussionmentioning
confidence: 99%